Scalings of the outer energy source of wall-turbulence - Cimarelli, A.; de Angelis, E.; Schlatter, Philipp; Brethouwer, G.; Talamelli, A.; Casciola, C. M. (ETC 2013 - 14th European Turbulence Conference, 2020)
By means of the multidimensional description given by the Kolmogorov equation we study the energy transfer physics and the production mechanisms of wall-turbulent flows at moderately high Reynolds numbers. Two driving mechanisms are identified for the energy fluxes. The first stronger one, here called driving scale-range (DSR), belongs to the near-wall cycle. As expected, its topology remains unaltered with Reynolds number while its intensity is found to slightly increase with Re. The second mechanism, here called outer scale-range (OSR), takes place in the overlap layer and highlights different features in agreement with the attached eddies hypothesis usually considered to describe the overlap dynamics.
CRIS-Team Scopus Importer:2023-03-21